Biomass of unconventional plants from Brazilian semiarid as substrate for hydrolytic enzymes production by Aspergillus niger under solid and submerged fermentation - Bruna dos Santos Menezes; Kátia dos Santos Morais; Aparecido Almeida Conceição; Juliana Gomes Barreto Souza Leite; Fábia Giovana do Val de Assis; Félix Gonçalves Siqueira; Patrícia Lopes Leal (Acta Scientiarum: Biological Sciences, 2021)
Aspergillus niger KIJH was grown in solid and submerged fermentation using leaves and roots (with and without bark) of plants typically from Brazilian semiarid as substrate to produce a multienzymatic extract, which was characterised for its potential biotechnological applications. Solid-state fermentation (SSF) was applied to select the most promising plants biomass as induction substrates for the production of hydrolytic enzymes by fungus. The best biomasses were used as substrate in submerged fermentation (SmF) assays at two scales. Samples of up scale fermented culture were partially purified by ultrafiltration and activity and pH and temperature stability of CMCase and xylanase were evaluated. A. niger KIJH produced hydrolytic enzymes under SSF containing unconventional plants biomass from Brazilian semiarid. In SmF conditions, maximum CMCase (0.264 U mL-1) and xylanase (1.163 U mL-1) activities were induced by Jacaratia corumbensis. Scaling up the SmF to 500 mL of medium was able to maintain constant the production of CMCase (0.346 U mL-1) and xylanase (1.273 U mL-1) on the fermented culture. Ultrafiltered and concentrated extract presented CMCase activities practically constant in all temperature ranges (30-80°C) and pH (3.0-9.0), while xylanase optimum activity temperature was 50°C and pH in the range of 3.0 to 5.0. CMCase activity remained stable for 24 hours at 50°C and xylanase was reduced in 53% after two hours incubation at the same temperature. CMCase and xylanase obtained by A. niger KIJH cultivated in submerged culture containing J. corumbensis as carbon source may have application in biotechnology processes that require enzymes that remain active under routine extreme conditions.